Historical film : a critical introduction - Stubbs, Jonathan (New York : Bloomsbury Academic, 2013)
Although precise definitions have not been agreed on, historical cinema tends to cut across existing genre categories and establishes an intimidatingly large group of films. In recent years, a lively body of work has developed around historical cinema, much of it proposing valuable new ways to consider the relationship between cinematic and historical representation. However, only a small proportion of this writing has paid attention to the issue of genre. In order to counter this omission, this book combines a critical analysis of the Hollywood historical film with an examination of its generic dimensions and a history of its development since the silent period. Historical Film: A Critical Introduction is concerned not simply with the formal properties of the films at hand, but also the ways in which they have been promoted, interpreted and discussed in relation to their engagement with the past.
Includes bibliographical references and index.
Includes filmography.
Keywords: Historical films -- United States -- History and criticism; Motion pictures and history